Trained immunity as a possible newcomer in autoinflammatory and autoimmune diseases pathophysiology - Beignon, Anne-Sophie; Galeotti, Caroline; Menager, Mickael M.; Schvartz, Adrien (Frontiers in Medicine, 2023)
Autoimmune disorders have been well characterized over the years and many pathways – but not all of them - have been found to explain their pathophysiology. Autoinflammatory disorders, on the other hand, are still hiding most of their molecular and cellular mechanisms. During the past few years, a newcomer has challenged the idea that only adaptive immunity could display memory response. Trained immunity is defined by innate immune responses that are faster and stronger to a second stimulus than to the first one, being the same or not. In response to the trained immunity inducer, and through metabolic and epigenetic changes of hematopoietic stem and progenitor cells in the bone marrow that are transmitted to their cellular progeny (peripheral trained immunity), or directly of tissue-resident cells (local innate immunity), innate cells responsiveness and functions upon stimulation are improved in the long-term. Innate immunity can be beneficial, but it could also be detrimental when maladaptive. Here, we discuss how trained immunity could contribute to the physiopathology of auto-immune and auto-inflammatory diseases.